The Relationship between Self-Concept and Self-Confidence in Islamic Religious Education Study Program Students - Azizi, Khoiri; Shittu, Sulayman Adeniran; Fawwaz, Ahmad Ghiyats (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the relationship between self-concept and self-confidence of students in the Islamic Religious Education Study Program. Methodology: The data collection used was a quantitative approach, which was carried out using a questionnaire method which was distributed to 75 respondents. Then to find out the relationship between variables X and Variable Y, use Product Moment. Main Findings: The results of the research analysis show that there is a positive and significant relationship between self-concept and self-confidence of students in the Islamic Religious Education Study Program, this is proven by the results ro of 0.234 which is consulted with the r table value at a good error level of 1% (0.296) or 5% (0.227) which means ro is greater than or equal to r table. Novelty/Originality of this study: This study highlights the importance of self-concept in building the self-confidence of Islamic Religious Education students, offering new insights for educators to develop more effective teaching strategies.